Laparoscopic Central Pancreatectomy and Pancreaticogastrostomy for the Management of a Proximally Migrated Pancreatic Stent - Gonzalez, Felipe; Mesleh, Marc G; Lukens, Frank J; Wallace, Michael B; Asbun, Horacio J; Stauffer, John Andrew (JOP. Journal of the Pancreas, 2013)
Context Pancreatic stents are used for both benign and malignant pancreatic disease but can be associated with complications such as proximal migration. Case report A 43-year-old female with benign biliary disease underwent prophylactic pancreatic stent placement after endoscopic retrograde cholangiopancreatography. This stent migrated proximally into the pancreatic duct and could not be retrieved by endoscopic measures. Therefore, she underwent surgical retrieval via a laparoscopic central pancreatectomy with pancreaticogastrostomy reconstruction. The procedure took 250 minutes with minimal blood loss. The postoperative course was uneventful and the patient was discharged on the sixth postoperative day without any evidence of pancreatic fistula. Conclusion Laparoscopic central pancreatectomy is a feasible option for the unusual indication of a retained proximally migrated pancreatic duct stent. Image: Pancreatic ductotomy with exposure of the impacted 5 Fr pigtail pancreatic duct stent.